2003
DOI: 10.1007/s00439-003-1065-7
|View full text |Cite
|
Sign up to set email alerts
|

Localized aggressive periodontitis is linked to human chromosome 1q25

Abstract: Localized aggressive periodontitis (LAP; previously known as localized juvenile periodontitis) is one of the rapidly progressive periodontal diseases. Certain forms of familial LAP show a simple Mendelian pattern of transmission. However, no gene mutation has been identified to be responsible for the LAP phenotype. As an initial step to identify a gene mutation associated with LAP, we have performed genetic linkage analysis with four multigenerational families exhibiting the LAP phenotype. Affected individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 21 publications
3
47
0
Order By: Relevance
“…Subsequently, our findings may not necessarily apply to CGD patients from other ethnicities and regions. Moreover, the abundance of autosomal recessive types of CGD here suggests the presence of co-segregated genes for periodontitis; similar to the previously described co-segregation of a neutrophil abnormality trait with localized aggressive periodontitis [33,34]. Furthermore, periodontitis has been reported with several rare genetic syndromes such as leukocyte adhesion deficiency, Ehler - Danlos syndrome type 8, and Lowe syndrome indicating the variety of genes that can predispose to periodontal disease [35].…”
Section: Discussionsupporting
confidence: 82%
“…Subsequently, our findings may not necessarily apply to CGD patients from other ethnicities and regions. Moreover, the abundance of autosomal recessive types of CGD here suggests the presence of co-segregated genes for periodontitis; similar to the previously described co-segregation of a neutrophil abnormality trait with localized aggressive periodontitis [33,34]. Furthermore, periodontitis has been reported with several rare genetic syndromes such as leukocyte adhesion deficiency, Ehler - Danlos syndrome type 8, and Lowe syndrome indicating the variety of genes that can predispose to periodontal disease [35].…”
Section: Discussionsupporting
confidence: 82%
“…LAP is a clinical and genetic heterogeneous group of periodontal disorders that can present with early periodontal disease accompanied by variable degree of neutrophil function abnormalities. Yet, the severe shin bruising observed in some members of this family is not seen in LAP and we have excluded chromosome 1q25, previously linked to LAP, 26 as a potential causal 27 We recently completed a genome-wide linkage scan in a different EDS VIII pedigree with a resulting linked region in chromosome 9. As yet, no gene mutation has been identified that could explain the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control genome wide association study suggested a role for GLT6D1 in aggressive periodontitis in Germans [15]. One linkage study in African American families [16] showed that aggressive periodontitis is linked to the marker D1S492, located on chromosome 1q. A susceptibility locus for aggressive periodontitis was determined between the markers D1S196 and D1S533.…”
Section: Introductionmentioning
confidence: 99%